PENGARUH LAMA PENYUNGKUPAN TERHADAP DAYA HIDUP SETEK TANAMAN LADA (Piper nigrum L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Arisiyantoro Arisiyantoro; HRA Mulyani; Rasuane Noor (EDUBIOLOCK, 2023)
Pepper (Piper nigrum L.) is a spice plant that has high economic value and has good prospects. The use of the right method will also optimize the growth of pepper seeds, one of the stages of pepper seedling is one of which is covering. The purpose of this study was to determine the effect of the length of coverage on the viability of pepper (Piper nigrum L.). This type of research was an experiment using a completely randomized block design (CRD) and using 3 treatments, one control and 5 replications. The research was conducted for 35 days from 23 March to 3 May 2020. The parameters observed were number of live cuttings, shoot height and root length. The data obtained were analyzed using the One Way Anava Test. The results showed that the length of covering had an effect on the viability of pepper cuttings (Piper nigrum L.).The results of this study can be used as a source of learning biology in the form of LKPD (Student Worksheet).